The Implementation of Inclusive Education for Children with Special Needs in SD Negeri Unggulan Mongisidi 1 Makassar - Jumriah, Jumriah; Fauziah, Puji Yanti (JPI (Jurnal Pendidikan Inklusi), 2024)
This study aims to reveal: (1) the background and foundation of the implementation of inclusive education for children with special needs at SDN Unggulan Mongisidi 1; (2) the collaborative role of key actors in implementing inclusive education for children with special needs at SDN Unggulan Mongisidi 1; and (3) the inclusive education model at SDN Unggulan Mongisidi 1. This research is qualitative in nature applying the case study design. This research was conducted at SDN Unggulan Mongisidi 1, which is a reference public primary school for children with disabilities in Makassar city. The informants of this study were the principal, class teachers, special mentor teachers and parents/guardians of students at SDN Unggulan Mongisidi 1. The data analysis technique used the Miles and Huberman interactive model analysis. Data collection techniques were carried out by in depth interviews, observation, and documentation studies. The results of this study are as follows: (1) the implementation of inclusive education for children with special needs at SDN Unggulan Mongisidi 1 has a physical and social background, and is based on juridical, philosophical and psychological foundations; (2) the form of collaboration between key actors is carried out by optimizing their respective functions and duties; and (3) the inclusive education implementation model used is the regular class model with pull out